Impact of Covid-19 on Oman’s Construction Industry - Al Amri, Tariq; Marey-Pérez, Manuel (Technium Social Sciences Journal, 2020)
COVID-19 is a global pandemic that changed the global economic perspective. The ongoing pandemic is indeed the major cause of project delays in the Middle East. A severe impact is being taken place in all industries. Therefore, this research covers the construction industry of Oman, the Impact of COVID-19 on the construction industry; the global impact of COVID-19 pandemic; the impact of global impact, and the prospects of Oman’s economy. The study covers the impact of COVID-19 on global and regional economies. The construction industry and its economic prospects are also discussed in the global pandemic of COVID-19. The secondary research critically insight the impact of coronavirus along with the construction business dimensions of Oman’s construction industry.